Local power and the location of subsidized renters in comparative perspective: public support for low- and moderate-income households in the United States, France, and the United Kingdom. Issue 10 (13th October 2022) - Freemark, Yonah; Steil, Justin
Abstract: In the context of worsening housing affordability for low- and moderate-income households, we assemble data from metropolitan areas in the United States, France, and the United Kingdom to analyze regional differences in the level and distribution of nationally supported affordable-housing units and renters with tenant-based housing benefits. We examine the location of subsidized renters comparatively, exploring how varying power arrangements between national and local governments over land-use and housing policy shape options for low-income renters. We find that US metropolitan areas are unique in the extent to which many municipalities exclude subsidized renters altogether; subsidized housing is disproportionately situated in areas with historically limited access to resources. The number of municipalities within metropolitan areas does not appear to impact the location of subsidized units, but the ability of localities to exclude is associated with their distribution.